Association of burnout and intention-to-leave the profession with work environment: A nationwide cross-sectional study among Belgian intensive care nurses after two years of pandemic. (January 2023) - Bruyneel, Arnaud; Bouckaert, Nicolas; Maertens de Noordhout, Charline; Detollenaere, Jens; Kohn, Laurence; Pirson, Magali; Sermeus, Walter; Van den Heede, Koen
Abstract: Background: Intensive care unit (ICU) nurses are at an increased risk of burnout and may have an intention-to-leave their jobs. The COVID-19 pandemic may increase this risk. Objective: The objective of this study was to describe the prevalence of burnout risk and intention-to-leave the job and nursing profession among ICU nurses and to analyse the relationships between these variables and the work environment after two years of the COVID-19 pandemic. Design: A national cross-sectional survey of all nurses working in Belgian ICUs was conducted between December 2021 and January 2022 during the 4th and 5th waves of the COVID-19 pandemic in Belgium. The Practice Environment Scale of the Nursing Work Index (PES-NWI) was used to measure the work environment, intention-to-leave the hospital and/or the profession was assessed. The risk of burnout was assessed using the Maslach Burnout Inventory scale including emotional exhaustion, depersonalisation, and reduced personal accomplishment. Setting: Nurses in 78 out of 123 Belgian hospital sites with an ICU participated in the survey. Participants: 2321 out of 4851 nurses (47.8%) completed the entire online survey. Results: The median overall risk of burnout per hospital site (high risk in all three subdimensions) was 17.6% [P25: 10.0 - P75: 28.8] and the median proportion of nurses with a high risk in at least one subdimension of burnout in Belgian ICUs was 71.6% [56.7–82.7]. A median of 42.9% [32.1–57.1] of ICU nurses stated that they intended-to-leave the job and 23.8% [15.4–36.8] stated an intent-to-leave the profession. The median overall score of agreement with the presence of positive aspects in the work environment was 49.0% [44.8–55.8]. Overall, nurses working in the top 25% of best-performing hospital sites with regard to work environment had a statistically significant lower risk of burnout and intention-to-leave the job and profession compared to those in the lowest performing 25% of hospital sites. Patient-to-nurse ratio in the worst performing quartile was associated with a higher risk for emotional exhaustion (OR = 1.53, 95% CI:1.04–2.26) and depersonalisation (OR = 1.48, 95% CI:1.03–2.13) and intention-to-leave the job (OR = 1.46, 95% CI:1.03–2.05). Conclusions: In this study, a high prevalence of burnout risk and intention-to-leave the job and nursing profession was observed after two years of the COVID-19 pandemic. Nevertheless, there was substantial variation across hospital sites which was associated with the quality of the work environment. Tweetable abstract : "Burnout & intention to leave was high for Belgian ICU nurses after 2 years of COVID, but wellbeing was better with high quality work environments and more favourable patient to nurse ratios".